Evaluation in Norway: A 25-Year Assessment - Askim, Jostein; Døving, Erik; Johnsen, Åge (Scandinavian Journal of Public Administration, 2021)
This article analyses the Norwegian government’s evaluation practice over the 25-year period from 1994 to 2018. Evaluations are mandatory for government ministries and agencies in Norway, with the government conducting some 100 evaluations annually. This article utilises data from a unique database to describe the development of the evaluation industry, focusing on the volume of evaluations, the most active commissioners and providers of evaluations, and the types of evaluations conducted. First, the analysis indicates that the volume of evaluations peaked in around 2010 and has subsequently decreased. As a possible consequence, information relevant to policy may be less publicly available than before. Second, ministries have commissioned relatively fewer evaluations in the last decade than in the years before, and executive agencies have commissioned relatively more. Third, the proportion of evaluations performed by consultants has risen, with that of research institutes falling.